Da pena capital à Misericórdia que converte e salva: A mudança do catecismo no artigo sobre a pena de morte feita pelo Papa Francisco - Bantim Oliveira, Antônio Edson; Alves de Araújo, Ricardo (Kairós: Revista Acadêmica da Prainha, 2021)
The paper’s purpose is to show the view of the Catholic Church about the death penalty controversy. The Church, both human and divine, is always concerned about the good of man and of society. Nonetheless, the Church is historical, and she follows history, assimilating customs and rules, also fashioning, structuring and building thoughts. Hence, in the assembling of her doctrine, she attempted to explain many subjects that constitute the complexity of human society. Among them is the question of the death penalty. The death penalty is based on a great tradition, even the Catechism of 1992 brought up again this question, saying that it should be applied in the collapse of all unemotional means. However, the theme brought a hardship time, in which proceeded for about 36 years, until 2018. Pope Francis declared the deep revocation of the doctrinal theme. In this perspective, we reflect the return of the primacy and inviolability of human life, moving closer and closer to the dynamics of Jesus Christ, the source of all Christian doctrine.